Judicial Oversight of Manifest Error in Administrative Decisions - المرسومي, عمار حسين علي (PROSPECTIVE RESEARCHES, 2024)
The French Council of State, in the field of overseeing discretionary authority of administration in exercising its presidential authority over its employees, resorted to a technical means represented by the theory of apparent error in judgment. This expanded the scope of judicial oversight over the administrative discretion in various areas. Although the Egyptian judiciary did not use the term "apparent error" in administrative decisions, it employed a distinctive term, namely, "manifest impropriety," to express the illegitimacy of administrative decisions. It also introduced the theory of "excess," which preceded its French counterpart in the field of judicial control over administrative decisions. The Iraqi judiciary effectively applied the theory of apparent error in administrative decisions, as evident in the rulings issued by the General Employees Discipline Board. The apparent error can be defined as a mistake committed by the administrative authority that is clear, obvious, and does not provoke discussion or debate. Various criteria for apparent error exist, including linguistic, personal, and objective standards. Over time, judicial oversight over the discretionary authority of administration in performing its duties and exercising its powers has evolved from leniency to severity. It began with monitoring the physical existence of facts, then progressed to legal conformity control of facts, and further intensified through legal oversight of the assessment of the significance of facts. Judicial precedents demonstrate the diverse areas of applying judicial oversight over apparent errors in administrative decisions, as detailed in this study.